A thenian educational values as consideration for social development (2016)
Ancient Athens was reputed to be a bright intellectual, educational and cultural center all over ancient Greece and beyond. The primary objective of its education was the cultivation of the person's mental, physical and moral qualities, with a view to helping the youth to become cerebral, physically strong, decent and then useful to his city and fellow citizens. The emphasis of Athenian education was preparing well-rounded citizens who were conscious of lofty values behind performing whatever task was asked of them. In contrast with many contemporary schools that focus on short-term outcomes, the Athenian school system took a lifelong view. Educational approach that aims at producing quality leaders and value-oriented people is hard-fought today. The place of proper values in relation to educational goals has been given very little attention by most educational institutions. Attitudes of growing number of parents and teachers are no help. In the attempt to attain personal goals, all eyes seem shut to development of those personal qualities that are most crucial to real community development: honesty, integrity, and the ability to work collaboratively. This article reviews the Athenian approach to education and posits that the values embedded in the Greeks’ basic education dictated the societal outcome of schooling in the ancient time. Then, with a discussion on Pericles’ Funeral Oration, a value assessment is presented. In sum, emphasis is placed on the social need for a value-driven education that involves an entire community in the article to demonstrate that coping effectively and creatively with emerging national and world trends requires more than possession of new knowledge and skills.